Pengaruh Metode Pengajaran Guru terhadap Motivasi Belajar Siswa SMP pada Pembelajaran Online - Nur Hanifah Asyri; Susandari (Bandung Conference Series: Psychology Science, 2023)
Abstract. During the Covid-19 pandemic, students' learning motivation during online learning activities has decreased somewhat. Learning motivation is a process in which a person performs an activity to learn. Various factors are estimated to affect the decline in student learning motivation during the Covid-19 pandemic, including the teacher’s teaching method. This study aims to see how much influence teacher’s teaching methods have on student learning motivation during online learning. The respondents in this study were 549 junior high school students in the city of Bandung. Respondent were obtained using Convenience Sampling. Online Teaching Method was measured using Online Teaching scale by Johnson & Aragon (2003). Learning Motivation was measured by modified instrument from Ilmi Khoir Purba (2017) referring to aspects of Learning Motivation by Schunk, Pintrich, and Meece (2012). The Correlation result was 0.598 that is classified as moderate, with contribution 35.8%. The level of motivation for learning junior high school students in the city of Bandung during online learning is classified as moderate. Abstrak. Selama pandemi Covid-19 motivasi belajar siswa selama kegiatan pembelajaran online terbilang menurun. Terdapat berbagai faktor yang diperkirakan dapat mempengaruhi menurunnya motivasi belajar siswa selama pandemi Covid-19, salah satunya adalah metode pengajaran guru. Untuk itu penelitian ini bertujuan untuk melihat seberapa besar pengaruh metode pengajaran guru terhadap motivasi belajar siswa selama pembelajaran online. Responden dalam penelitian ini berjumlah 549 siswa, yang berstatus sebagai Siswa SMP di Kota Bandung. Data responden diperoleh menggunakan Convenience Sampling. Metode Pengajaran Online diukur menggunakan alat ukur yang mengacu pada aspek Pengajaran Online oleh Johnson & Aragon (2003). Motivasi belajar diukur menggunakan hasil modifikasi alat ukur dari Ilmi Khoir Purba (2017) yang mengacu pada aspek Motivasi Belajar oleh Schunk, Pintrich, dan Meece (2012). Hasil korelasi sebesar 0.598, dimana nilai korelasi tergolong sedang, dengan nilai kontribusi sebesar 35.8%. Tingkat motivasi belajar siswa SMP di Kota Bandung selama pembelajaran online ini tergolong dalam kategori sedang.